Crisis management. (c2018) - Jibai, Ali Mohamad (2018)
The study examines the relationship between crisis preparedness and corporate sustainability in the context of the Lebanese insurance sector, and investigates the role of leadership style in governing the relationship between both variables. Crisis management has become a critical element of survival for these firms and proactive crisis management strategies are being utilized to evade future crises and uphold sustainability. Therefore, one of the best reinsurance brokerage firms in Lebanon was chosen as a testbed to assess the relationship between crisis preparedness and corporate sustainability, and to recommend whether transformational or transactional leadership style is a better mediator for explaining this relationship. A cross-sectional questionnaire was designed to assess the significance of the relationships between the afore-mentioned variables, namely: (1) leadership style, (2) crisis preparedness, and (3) corporate sustainability. The survey was distributed to all the 87 middle and top managers at the reinsurance brokerage firm under study, out of which 62 complete responses were collected, representing 71% of this experienced employees’ population. The findings indicate the significant relationship between crisis preparedness and corporate sustainability only in the presence of one of the leadership styles, and demonstrate the privileged significance of transformational leadership over the transactional leadership when applying both as double mediators. Accordingly, in addition to a proper implementation of well-written processes, it is advisable that managers at all levels receive leadership training to improve the transformational skills as a main component of their leadership characteristics in order to enhance the opportunities for organizational sustainability.